2019
DOI: 10.1209/0295-5075/125/28001
|View full text |Cite
|
Sign up to set email alerts
|

Controlling stability and transport of magnetic microswimmers by an external field

Abstract: We investigate the hydrodynamic stability and transport of magnetic microswimmers in an external field using a kinetic theory framework. Combining linear stability analysis and nonlinear 3D continuum simulations, we show that for sufficiently large activity and magnetic field strengths, a homogeneous polar steady state is unstable for both puller and pusher swimmers. This instability is caused by the amplification of anisotropic hydrodynamic interactions due to the external alignment and leads to a partial dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…This result intimately relates vanishing shear viscosity to the onset of collective motion, albeit only in infinite systems: CKT treats the driving flow as homogeneous and infinite and is thus insensitive to the size of the system. Moreover, with few exceptions (31,32), CKT studies of rheology to date have ignored interparticle interactions. Formulating a CKT in confinement properly is technically demanding.…”
Section: Current Theoriesmentioning
confidence: 99%
“…This result intimately relates vanishing shear viscosity to the onset of collective motion, albeit only in infinite systems: CKT treats the driving flow as homogeneous and infinite and is thus insensitive to the size of the system. Moreover, with few exceptions (31,32), CKT studies of rheology to date have ignored interparticle interactions. Formulating a CKT in confinement properly is technically demanding.…”
Section: Current Theoriesmentioning
confidence: 99%
“…For example, the magnetic alignment, combined with a micro-aerotactic swimming response, qualifies such micro-swimmers as a promising vector for targeted drug therapy [32]. Recently, it was proposed, on theoretical grounds, that a suspension of such magnetotactic bacteria could display original magneto-rheological properties [33,34], novel pattern formation [35] and hydrodynamic instabilities [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically it is shown that MTB might present original magnetorheological properties and present novel collective behavior. [ 378–381 ] Experimentally, the MTB were shown to behave as rotary motors in oil–water emulsions for example and therefore their behavior in complex medium is an open field. [ 382 ] In this line, taking into account that among MTB strains they have different properties and needs, the same diversity is most likely to be translated to different collective behaviors which if controllable are of interest for the field or robotics.…”
Section: Discussion and Future Workmentioning
confidence: 99%